Avaliação de malhas de aterramento de subestações : uma abordagem probabilística do risco de fatalidades - Braulio Roberto de Melo Coutinho (2021)
This work presents a discussion about the application of the probabilistic method for risk analysis in substation grounding systems, in comparison to the deterministic method for mesh design. In the probabilistic approach, the dangerous potentials that may occur as a result of a short circuit, are not only compared with maximum allowable voltages, but transformed into a risk analysis. To determine the risk of fatality associated to grounding system, it is necessary to calculate the probabilities of coincidence and fibrillation. The probability of coincidence is defined as the possibility of a person being exposed to a grounded asset or being in a region that may have a potential difference during the occurrence of a ground fault. The probability of fibrillation estimates the likelihood that the victim will suffer ventricular fibrillation if subjected to step or touch voltage. To debate the subject, the work first contextualizes the current methodology through the presentation of the main points of “NBR 15751: Substation earthing system - requirements”. Then, the probabilistic approach is presented through a review of articles published in recent years and international standards that treat the subject. A case study contemplating a real design of a grounding grid for two 138 kV substations sharing the same yard, is then presented. The project is developed from a deterministic perspective and, subsequently several risk analysis are made through the probabilistic approach. Finally, a set of existing substations under the probabilistic approach is also assessed. The results show that risk assessment methodology presents itself as a great tool to quantify the danger and allow the designer to make decisions with greater security. Another finding is that substations with higher clearing time may present a higher risk of fibrillation, however, due to the low probability of coincidence, the risk of fatality is within the international standards acceptable level.